Scapular Stabilzation Exercises for the Management of Bilateral Snapping Scapula Syndrome - pokharel, Mukesh; sharma, Rasmita; sapkota, Nabin; Bhurtel, Bidur; Chandra, Avinash; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
This case reports depicts the effect of scapular stabilization regimen for managing clinical symptoms of scapular dyskinesis presenting with crepitus during shoulder movement. A 35 old banker with history of peri scapular, shoulder and coracoid area pain with auditory joint noise visited our department. Scapular stabilization exercise regimen with emphasis on normalizing anatomical symmetry, scapular motor control was done for 40 mins, three times a week for 8 weeks. Follow up was maintained once a month after that or as per the need. Measurements included scapular deviations, muscle strength, pain intensity, quality of life and global rate of change. These changes were assessed at the beginning before the intervention, 8 weeks after treatment and during 1 year follow-up. Data shows favourable improvement on pain, strength , scapular symmetry and quality of life. Thus, it can be concluded that the scapular stabilization exercise is helpful in alleviating symptoms related to scapular dyskinesis and snapping scapula syndrome.